An External Sorting Algorithm Using In-Place Merging and With No Additional Disk Space - Islam, Md. Rafiqul; Raquib Uddin, S. M. (Malaysian Journal of Computer Science, 2005)
This paper presents an external sorting algorithm using linear-time in-place merging and without any additional disk space. The algorithm uses quick sort to produce runs in the first phase. In the second phase it uses special verification technique and uses in-place merging technique to reduce the average time complexity and disk I/Os especially the output (write) operations. The I/O and time complexities are analysed and compared with another algorithm [5] which also uses no additional disk space.